Central bank communication and the perception of monetary policy by financial market experts - Sandra Schmidt; Dieter Nautz (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
This paper investigates why financial market experts misperceive the interest rate policy of the European Central Bank (ECB). Assuming a Taylor-rule-type reaction function of the ECB, we use qualitative survey data on expectations about the future interest rate, inflation, and output to discover the sources of individual interest rate forecast errors. Based on a panel random coefficient model, we show that financial experts have systematically misperceived the ECB's interest rate rule. However, although experts tend to overestimate the impact of inflation on future interest rates, perceptions of monetary policy have become more accurate since clarification of the ECB's monetary policy strategy in May 2003. We find that this improved communication has reduced disagreement over the ECB's response to expected inflation during the financial crisis.
Keywords: E47; E52; E58; C23; 330; Central bank communication; Interest rate forecasts; Survey expectations; Panel random coefficient model; Zinspolitik; Geldpolitik; Staatliche Information; Finanzanalysten; Erwartungstheorie; Schätzung; EU-Staaten